2017
DOI: 10.1371/journal.pone.0186569
|View full text |Cite
|
Sign up to set email alerts
|

Morphological study of the eye and adnexa in capuchin monkeys (Sapajus sp.)

Abstract: The objective of this study was to describe the anatomic and histologic features of the Sapajus sp. eye, comparing similarities and differences of humans and other species of non-human primates for biomedical research purposes. Computed tomography (CT) of adnexa, eye and orbit live animal, as well as formolized pieces of the same structures of Sapajus sp. for anatomical and histological study were also performed. The anatomical description of the eye and adnexa was performed using the techniques of topographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
1
3
0
1
Order By: Relevance
“…CT allowed identification mainly of the adnexa; and a detailed study was only possible in the live animal, regardless of the presence of iodinated contrast. This is in agreement with Nascimento et al [17], who reported no influence of iodinated contrast for the interpretation of Sapajus sp. CT images in the soft tissue window.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…CT allowed identification mainly of the adnexa; and a detailed study was only possible in the live animal, regardless of the presence of iodinated contrast. This is in agreement with Nascimento et al [17], who reported no influence of iodinated contrast for the interpretation of Sapajus sp. CT images in the soft tissue window.…”
Section: Discussionsupporting
confidence: 93%
“…The influence of habitat was also noted by the brownish coloration of the bulbar conjunctiva of crab-eating foxes, also noted for Sapajus sp. and capybara eyes [15, 17], but present only in exposed areas of the canine conjunctiva, or in abnormal or chronic conditions [2022]. Species inhabiting temperate forests, such as the American beaver, possess pigmentation limited to the limbal-based region, since those animals does not receive the same amount of sunrays in their natural environment, compared to neotropical species [15, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Os PNM estão distribuídos na América Central e do Sul e apresentam uma grande diversidade em padrões de coloração, localização e tamanho das espécies. Por outro lado, os PVM são de ocorrência dos continentes asiático e africano (Nunes & Catão-Dias, 2014;Guimarães, 2007;Rylands, 2014;Lynch et al, 2014;Silva et al, 2017).…”
Section: Resultsunclassified
“…G.Orbital Area (OA). 22/7 ab, where a and b are half the orbital length and width, respectively (Silva et al, 2017;Lantyer-Araujo et al, 2019). H. Interorbital distance CT3D:…”
Section: Orbital Parametermentioning
confidence: 99%
“…Morphometric Assessments.Three heads of cattle compared to three heads of domestic pigs were fixed using 0.1 mL of 10 % buffered formalin (Lantyer-Araujo et al, 2019). Macroscopic evaluation of the visual system was performed using a topographic dissection and exenteration method, with a Digital Vernier Caliper (Silva et al, 2017) the eye was sectioned in the sagittal plane, including the optic nerve. All steps were photographed with a camera.…”
Section: Orbital Parametermentioning
confidence: 99%